2022
DOI: 10.3389/fpls.2022.883209
|View full text |Cite
|
Sign up to set email alerts
|

Root Pulling Force Across Drought in Maize Reveals Genotype by Environment Interactions and Candidate Genes

Abstract: High-throughput, field-based characterization of root systems for hundreds of genotypes in thousands of plots is necessary for breeding and identifying loci underlying variation in root traits and their plasticity. We designed a large-scale sampling of root pulling force, the vertical force required to extract the root system from the soil, in a maize diversity panel under differing irrigation levels for two growing seasons. We then characterized the root system architecture of the extracted root crowns. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…( Berry et al 2021 ). Further, we explored the phenotypic correlation of root lodging with a variety of published above-ground traits ( Leiboff et al 2015 ), RSA traits ( Zheng et al 2020 ), root pulling force (RPF) data ( Woods et al 2022 ), and previously unpublished brace root trait data we collected from prior years ( Supplemental Text S1 and Table S4 ). The correlations of these traits with root lodging were generally low (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…( Berry et al 2021 ). Further, we explored the phenotypic correlation of root lodging with a variety of published above-ground traits ( Leiboff et al 2015 ), RSA traits ( Zheng et al 2020 ), root pulling force (RPF) data ( Woods et al 2022 ), and previously unpublished brace root trait data we collected from prior years ( Supplemental Text S1 and Table S4 ). The correlations of these traits with root lodging were generally low (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…( Shah et al 2019 ). For root strength, we compared the overlap between the 118 candidate genes identified in the current study with those from a GWAS for RPF, a proxy trait that reflects root strength under different irrigation treatments (Supplemental Table S4 of Woods et al 2022 ); only a single candidate gene Zm00001eb191650 was identified in both studies. This gene is a maize homolog of an Arabidopsis gene, AtPHO1 involved in both phosphate and cytokinin signaling pathways; a mutant of this gene exhibits reduced root length when compared with wild type ( Lan et al 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“… Quantitative variation in lignin content in maize root systems from a field study of 358 maize inbred lines. A description of the experiment can be found in Woods et al (2022) . …”
Section: How Can More Carbon Be Retained In Soil and Biomass?mentioning
confidence: 99%